Effect of different foliar zinc application at different growth stages on seed zinc concentration and its impact on seedling vigor in rice - Boonchuay P. (2014)
This study evaluated how zinc (Zn) concentration of rice (Oryza sativa L.) seed may be increased and subsequent seedling growth improved by foliar Zn application. Eight foliar Zn treatments of 0.5% zinc sulfate (ZnSO4 · 7H2O) were applied to the rice plant at different growth stages. The resulting seeds were germinated to evaluate effects of seed Zn on seedling growth. Foliar Zn increased paddy Zn concentration only when applied after flowering, with larger increases when applications were repeated. The largest increases of up to ten-fold were in the husk, and smaller increases in brown rice Zn. In the first few days of germination, seedlings from seeds with 42 to 67 mg Zn kg-1 had longer roots and coleoptiles than those from seeds with 18 mg Zn kg-1, but this effect disappeared later. The benefit of high seed Zn in seedling growth is also indicated by a positive correlation between Zn concentration in germinating seeds and the combined roots and shoot dry weight (r = 0.55, p < 0.05). Zinc in rice grains can be effectively raised by foliar Zn application after flowering, with a potential benefit of this to rice eaters indicated by up to 55% increases of brown rice Zn, and agronomically in more rapid early growth and establishment. © 2013 Copyright Japanese Society of Soil Science and Plant Nutrition.